2014
DOI: 10.1159/000363368
|View full text |Cite
|
Sign up to set email alerts
|

Puberty-Related Changes in Cortisol, Dehydroepiandrosterone, and Estradiol-17β Secretions within the First Hour after Waking in Premenarcheal Girls

Abstract: Objective: The onset of menstruation is the hallmark of female pubertal development. The present study determined whether pubertal girls experience adrenocortical and ovarian steroid secretions within their first waking hour before getting their period, similar to those observed in adult females with regular cycles. Methods: Cortisol, dehydroepiandrosterone (DHEA), and estradiol-17β concentrations were measured in saliva samples collected after awakening (0, 30, and 60 min after awakening) from 158 normal prem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…A trend can be seen though to slight higher cortisol values in the older adolescents group which goes along with the fact of increasing cortisol levels with age. Additionally higher cortisol serum levels have been described in postpubertal children [18] However the effect of steroid hormones and pubertal timing is not clear yet . Pubertal timing is a complex process that cannot be generalized to one effect.…”
Section: Discussionmentioning
confidence: 99%
“…A trend can be seen though to slight higher cortisol values in the older adolescents group which goes along with the fact of increasing cortisol levels with age. Additionally higher cortisol serum levels have been described in postpubertal children [18] However the effect of steroid hormones and pubertal timing is not clear yet . Pubertal timing is a complex process that cannot be generalized to one effect.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the CAR and testosterone, DHT, epitestosterone (Epi-T), and dehydroepiandrosterone (DHEA) levels during the post-awakening period, a set of saliva samples (immediately on awakening and 30 and 60 min after awakening) was consecutively collected from men with AGA (t0, t1, and t2) and at a single time point (t0) from hairy controls. Each participant was instructed on the procedures and precautions for saliva collection described in previous studies [32,33]. Each participant was also asked to submit their saliva samples at each scheduled visit for hair collection and collect their saliva samples on one of the working days, with a minimum volume of 1.5 ml of saliva provided at each time point.…”
Section: Collection Of Saliva Samplesmentioning
confidence: 99%
“…The cortisol, testosterone, DHT, Epi-T, and DHEA concentrations in the collected hair and saliva samples were determined using radioimmunoassay by modifying the method used in previous studies [32,33]. DHT assays were conducted after the selective inactivation of testosterone with an aqueous potassium permanganate solution [38].…”
Section: Steroid Riamentioning
confidence: 99%
“…An increase in the ratio of salivary cortisol/cortisone during the first year of life, followed by stability throughout childhood and into young adult life, has been described, while salivary cortisol concentrations have variably been associated with sex, pubertal development and body mass index. [8][9][10][11][12][13][14][15] Adult studies have reported that salivary cortisone is a superior marker of serum cortisol than salivary cortisol, that salivary cortisol may be undetectable in healthy young men when serum cortisol concentrations fall below 74 nmol/L while salivary cortisone remains detectable, and that the use of salivary cortisone allows monitoring of hydrocortisone therapy without the risk of artificially elevated salivary cortisol concentrations due to saliva contamination with hydrocortisone. 7 It was the purpose of this study to determine, in the paediatric age group, which salivary biomarker correlated most strongly with serum cortisol, whether either was undetectable during waking hours and whether age and gender should be considered in the design of a study to generate reference data for use in clinical practice.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…To our knowledge, there are few data describing salivary cortisone concentrations in healthy children. An increase in the ratio of salivary cortisol/cortisone during the first year of life, followed by stability throughout childhood and into young adult life, has been described, while salivary cortisol concentrations have variably been associated with sex, pubertal development and body mass index 8‐15 …”
Section: Introductionmentioning
confidence: 99%